An introduction to English morphology : words and their structure - Carstairs- McCarthy, Andrew (b)
What exactly are words? Are they the things that get listed in dictionaries, or are they the basic units of sentence structure? Andrew Carstairs-McCarthy explores the implications of these different approaches to words in English.
Includes bibliographical reference and idex
Keywords: English; English language -- Morphology